Analisis Strategi Penghimpunan Wakaf Saham di Indonesia - Nurman Hakim (Badan Wakaf Indonesia, 2020)
Waqf is potentially because the number of Muslims reaches 87 percent of peoples in Indonesia. Share waqf also called stock waqf is one of the productive waqfs in the Islamic stock market but fundraising of share waqf is still low. Their problem is because publication and inclusion level about share waqf is not enough, besides share waqf begins emergence in Indonesia. This research tries to identify important factors and suitable strategies to share waqf’s fundraising in Indonesia. The research is field research which is used a qualitative approach, with an analysis method is the Analytic Network Process (ANP). The respondent of this research is divided into three categories which is, securities company, nazhir, and regulator.